Bohler's and Gissane Angles in the Indian Population - Sengodan,Vetrivel C.; Amruth,K. H.; Karthikeyan
Objective: The aim of our study is to determine the normal ranges of the calcaneal parameters in the Indian population, and to compare the results with the data in the literature. Materials and Methods: The study was conducted at Coimbatore Medical College Hospital, Coimbatore on the feet (324 in number) of male and female Indian adults. Lateral view of the ankle was taken using a digital X-ray machine. Two parameters namely Bohler`s and Gissane angles were measured, independently by two radiologists to prevent inter-observer variation. Results: The Bohler`s and Gissane angles for the Indian population are statistically different from those seen in the published data for other population groups, as evidenced by the P value (P < 0.05). Conclusion: Calcaneal parameters specific to the Indian population have to be taken into consideration by the orthopedic surgeon to improve the standard of calcaneal fracture treatment in India.